The First Attested Extraction of Ancient DNA in Legumes (Fabaceae) - Mikić, Aleksandar M. (Frontiers in Plant Science, 2015)
Ancient DNA (aDNA) is any DNA extracted from ancient specimens, important for diverse evolutionary researches. The major obstacles in aDNA studies are mutations, contamination and fragmentation. Its studies may be crucial for crop history if integrated with human aDNA research and historical linguistics, both general and relating to agriculture. Legumes (Fabaceae) are one of the richest end economically most important plant families, not only from Neolithic onwards, since they were used as food by Neanderthals and Paleolithic modern man. The idea of extracting and analysing legume aDNA was considered beneficial for both basic science and applied research, with an emphasis on genetic resources and plant breeding. The first reported successful and attested extraction of the legume aDNA was done from the sample of charred seeds of pea (Pisum sativum) and bitter vetch (Vicia ervilia) from Hissar, southeast Serbia, dated to 1,350 - 1,000 Before Christ. A modified version of cetyltrimethylammonium bromide (CTAB) method and the commercial kit for DNA extraction QIAGEN DNAesy yielded several ng μl-1 of aDNA of both species and, after the whole genome amplification and with a fragment of nuclear ribosomal DNA gene 26S rDNA, resulted in the detection of the aDNA among the PCR products. A comparative analysis of four informative chloroplast DNA regions (trnSG, trnK, matK and rbcL) among the modern wild and cultivated pea taxa demonstrated not only that the extracted aDNA was genuine, on the basis of mutation rate, but also that the ancient Hissar pea was most likely an early domesticated crop, related to the modern wild pea of a neighbouring region. It is anticipated that this premier extraction of legume aDNA may provide taxonomists with the answers to diverse questions, such as leaf development in legumes, as well as with novel data on the single steps in domesticating legume crops worldwide.